Australian child protection services: A game without end. (9th December 2011) - Hansen, Patricia; Ainsworth, Frank
This article argues that Australian child protection services are based on an error of logical typing. Across time, this has led to an over‐reliance on mandatory reporting legislation, a forensic/investigative/prosecutorial model of practice, a risk‐averse organisational culture and zero tolerance of any imperfections in parenting practices which are defined as child abuse and neglect regardless of their severity. All of these positions ignore powerful social stressors that surround complex family situations where abuse and neglect can occur. It is proposed that this error of logical typing is confirmed by the well‐documented fact that Australian child protection services have for more than two decades been unable to prevent or reduce the incidence of child abuse and neglect. For this article, New South Wales is used as the exemplar state.